PENGARUH EMOTIONAL BRANDING TERHADAP LOYALITAS PELANGGAN PRODUK HERBAL RAHSA NUSANTARA - Yaritsha Nafhan Thyola; Roni Kastaman; Faizal Syahmurman (Universitas Galuh, 2023)
The growth of herbal products in Indonesia is increasing every year causing the competition between herbal product companies to be increasingly tight. One of the herbal product companies in Indonesia is Rahsa Nusantara, but the growth in the category of loyal customers is not so significant. The research was conducted at the Rahsa Nusantara company in the range of January to August 2022. This study aims to determine the effect of emotional branding on Rahsa Nusantara's customer loyalty by using a simple linear regression method. The population in this study are Rahsa Nusantara customers who have made a minimum of one transaction. Collecting data using a questionnaire with a Likert scale. The results of the research findings that emotional branding can affect customer loyalty positively significantly with the highest emotional branding aspect in the vision aspect is known by correlation test. The results of the regression test resulted in a regression coefficient with a value of 0.462, indicating that each addition of one unit to the emotional branding variable will increase the value of customer loyalty by 0.462. The coefficient of determination found at 32% means that customer loyalty is only influenced by 32% by emotional branding. Thus, future research needs to examine other than emotional branding variables.